AUTHORITY OF INTELLECTUAL PROPERTY CONSULTANTS - Ervin Setiawan (Yuridika, 2016)
Intellectual Property Consultants appointed by the Ministry of Law and Human Rights is an office that has a limited authority to carry out their duties; The appointment of IPR consultant are intended to assist Ministry of Law and Human Rights in resolving the matter on IPR registration. Due to the reason that IPR is the scope of Ministry of Law and Human Rights authority, the one which has the authority to appoint someone as IPR Consultant is also Ministry of Law and Human Right. Appointment of IPR Consultant should be specially granted for Law School Graduate due to the reason that Consultant shall understand and able to execute the procedure of authority and regulation that limits its authority in running Consultant position. In carrying out its duties, IPR Consultant will be closely related to legal action and must strictly comply with the Law and assume responsibility given by the client. The duties and responsibilities attached to IPR Consultant have a legal consequence. In conducting its duties, IPR Consultant shall be able to read and implement the regulation enforced by the government.